Four new Luticola taxa (Bacillariophyta) from Maritime Antarctica - Zidarova, Ralitsa; Levkov, Zlatko; van De Vijver, Bart (Phytotaxa, 2014)
The paper describes four new Luticola taxa from the South Shetland Archipelago, Antarctica: Luticola neglecta sp. nov., L. bogaertsiana sp. nov., L. contii sp. nov. and L. olegsakharovii sp. nov. All new taxa are studied using both light and scanning electron microscopy and compared to other morphologically similar species from (sub-)Antarctica and elsewhere in the world. Data on their ecology and biogeography are added.